A rapid and scalable rice blast diagnostic tool - Timely disease identification point-of-care system (TIDIS) - Onaga, Geoffrey; Saunders, D.; Paajanen, P. (Africa Rice Center, 2024)
Rapid and cost-effective sequencing of pathogen genomes has become a fundamental aspect of plant health management in well-resourced settings. This technique needs to be extended to developing countries in order to limit crop losses and improve food security. The combination of pathogen diagnostics and epidemiology with advanced digital disease detection systems has the potential to greatly enhance continuous monitoring, prompt diagnosis, and real-time tracking of crop diseases in regions of the South that have limited access to well-equipped laboratories. AfricaRice and JIC are developing TIDIS, a portable and scalable point-of-care management system for disease identification, under PHI. TIDIS serves as monitoring system that delivers genotypic information of both the host and the pathogen for each field from which the pathogen is isolated and uses this information for epidemiological reconstruction. This facilitates a quick understanding of host specificity of the pathogen on the crop varieties grown in a specific region, thereby improving the effective management of crop diseases. We conducted a pilot of TIDIS on rice blast, a major yield limiting pathogen affecting rice worldwide.